English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Hey, this problem was/is a tough one for me!
It one of those PEMDAS promblems... I thought I had them "down pack" but now look.
Can you do this one for me and explain it
thank you so much :)

2007-02-06 15:06:24 · 9 answers · asked by OnSomeLousyPlanet 1 in Science & Mathematics Mathematics

9 answers

Do the work within the brackets first:
41-4[4+3(2)]
41-4[4+6]
41-4(10)
41-40=1

I hope this helps!

2007-02-06 15:14:18 · answer #1 · answered by Anonymous · 5 0

41 - 4[(6 - 2) + 3(5 - 3)] Well according to PEMDAS, you solve the equations in the parentheses first.
41-4[(4) + 3(2)] Although brackets aren't in PEMDAS, you have to do brackets after parentheses. However, you have to solve the equation inside the brackets. Remember, Multiplication comes before addition so...
41 - 4[4 + 6] Now add the numbers in the brackets
41 - 4[10] Again, Multiplication/Division comes before Addition/Subtraction so its...
41 - 40 So the answer is...
1

Hope this helps!

2007-02-06 23:24:14 · answer #2 · answered by ¡Jessica! 4 · 1 0

start with all the expressions in the Brackets
then do each operations required in the parenthesis and finally multiple the 3 with the sum in the paranthesis
[(6-2) + 3(5-3)]
6-2=4 + 3(5-3) = 3(2) = 6
4 + 6 = 10

41 - 4 (10) = 41 - 40 = 1

2007-02-06 23:21:41 · answer #3 · answered by manuel w 2 · 1 0

You do the problems inside the bars. Like first do the ( ) like (6-2)= 4 then the other ( ) ok since you have a 3 you do this [ 4+3(2)] you x 3 by 2 then add 4. THen you got your anwer inside the bars so you have 41-1[a] you subtract then, x the answer to the [a] like b[a]=c and c is your answer. Its been a while but im thinking thats it tell me what you got.

2007-02-06 23:21:16 · answer #4 · answered by everlasting_matchstick 3 · 1 0

work the parenthesis first so...

6-2=4 and 5-3=2 3(2)= 6

4+6=10 now multiply this by the 4 on the outside
4(10)=40 so add this to the equation
41-40=1 and that's your answer
always try to get rid of the parenthesis first

2007-02-06 23:20:54 · answer #5 · answered by #2 on the way! due 12/28 3 · 1 0

41 - 4[(6 - 2) + 3(5 - 3)]
brackets:

=41 - 4[(4) + 3(2)]
=41 - 4[10]

multiply/divide:

=41 - 40

add/subtract:

=1

2007-02-06 23:16:12 · answer #6 · answered by Anonymous · 1 0

resolve first paren:
41 - 4[4+3(2)]
2nd resolution
41- 4[10]
3rd step
41 - 40 = 1 final

2007-02-06 23:16:07 · answer #7 · answered by want2no 5 · 1 0

its 1.

2007-02-06 23:16:06 · answer #8 · answered by Jen 2 · 1 0

1 is the answer, explaination to follow shortly

EDIT: just look at above answer

2007-02-06 23:14:57 · answer #9 · answered by Bob L 2 · 3 0

fedest.com, questions and answers